Perawatan Internal Bleaching Menggunakan Teknik Walking Bleach Pada Gigi Insisif Sentral Kanan Rahang Atas (Case Report) - Rudy Djuanda (Maranatha Christian University, 2019)
Tooth discoloration is defined as extrinsic or intrinsic staining based on localization and etiology, appearance, severity and adhesion to the tooth structure. Tooth discoloration is a cosmetic problem and the teeth whitening procedure is more conservative than the restorative method. Tooth discoloration, especially those treated endodontically is a matter of concern for patients and dentists. Among the various bleaching techniques, the technique of